2022
DOI: 10.1186/s12876-022-02258-1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of primary signet ring cell carcinoma of colon and rectum: a case control study

Abstract: Background Primary signet ring cell carcinoma of the colon and rectum (PSRCCR) is rare, usually diagnosed at advanced stage with poor outcomes. We aimed to find possible diagnostic clues in order to help diagnosis. Methods A retrospective study of PSRCCR patients from 1993 to 2018 was reviewed at a single tertiary center. Colorectal adenocarcinoma patients as control group with 1:4 ratio was also enrolled. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…The incidence of SRCC in our CRC population (1.32%) was similar to the one reported in the world literature (0.3%-4.6%) (10-17) with only one series showing an unusual higher rate (18%) (28). The reported sex prevalence is heterogeneous in the literature (9,12,12,21,(29)(30)(31); in our work, the female to male ratio was 25 to 14 (1.8:1). In line with some previous studies, in our cohort, SRCC showed higher incidence among elderly patients (mean age: 69.9 years); on the contrary, other authors demonstrated younger patients (mean age: 39 to 42 years) to be the most affected target-population advocating for a major local aggressiveness and predisposition to peritoneal carcinomatosis (9,(30)(31)(32)(33)(34)(35)(36).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The incidence of SRCC in our CRC population (1.32%) was similar to the one reported in the world literature (0.3%-4.6%) (10-17) with only one series showing an unusual higher rate (18%) (28). The reported sex prevalence is heterogeneous in the literature (9,12,12,21,(29)(30)(31); in our work, the female to male ratio was 25 to 14 (1.8:1). In line with some previous studies, in our cohort, SRCC showed higher incidence among elderly patients (mean age: 69.9 years); on the contrary, other authors demonstrated younger patients (mean age: 39 to 42 years) to be the most affected target-population advocating for a major local aggressiveness and predisposition to peritoneal carcinomatosis (9,(30)(31)(32)(33)(34)(35)(36).…”
Section: Discussionsupporting
confidence: 88%
“…more than 50% of the extracellular space, signet-ring cell carcinoma (SRCC) characteristically shows intracellular mucin accumulation and peripheral arrangement of the nuclei in more than 50% of tumor cells (4)(5)(6)(7)(8). SRCCs have been frequently described in the gastrointestinal tract (especially stomach) but also in the breast, lung, gallbladder, pancreas, ovary, cervix, urinary system and salivary glands (5,9). The large bowel represents a further, rare site of occurrence.…”
mentioning
confidence: 99%
“…Signet ring cell cancer (SRCC) tends to be detected at a late stage, resulting in a poor prognosis (Tung et al , 1996). SRCC cells are shaped like a signet ring; the ‘signet’ portion of the ring is formed by the nucleus pushing into the cell wall due to internal pressure from excess intracytoplasmic mucin (Benesch and Mathieson, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal SRCC is a distinct subtype of colorectal cancer. According to previous reports, colorectal SRCC presents as high-grade carcinoma and is more commonly associated with lymphatic invasion, vascular invasion, perineural invasion, and more advanced tumor stage [ 36 , 37 ]. Besides, SRCC is a significantly prognostic factor for CRC [ 37 ].…”
Section: Discussionmentioning
confidence: 99%